Herbs used for behaviour modifying activity - Singh A.; Tripathi S.; Singh P.N. (My University, 2025)
Herbs have been highly valued and used regularly for thousands of years by the peoples of the world as the medicine of the masses. Man has always searched for that herb that heals the body and soothes the mind and nature is a rich source of biological and chemical diversity and a number of plants in the world have been used in traditional medicine remedies for various diseases. This work constitutes a literature review on medicinal plants showing behavior modifying properties such as anxiety, depression, seizures, poor memory, dementia, insomnia even though these herbs may have many other therapeutic effects. The review has been compiled using references from major databases like Chemical Abstracts, Medicinal and Aromatic Plants Abstracts, PubMed, Scirus, Google scholar, Open J Gate, Scopus, Science Direct and Online Journals.